Subcellular hot spots of GPCR signaling promote vascular inflammation (2020)
G-coupled protein receptors (GPCRs) comprise the largest class of druggable targets. Signaling by GPCRs is initiated from subcellular hot spots including the plasma membrane, signalosomes and endosomes to contribute to vascular inflammation. GPCR-G protein signaling at the plasma membrane causes endothelial barrier disruption and also cross-talks with growth factor receptors to promote proinflammatory signaling. A second surge of GPCR signaling is initiated by cytoplasmic NFκB activation mediated by β-arrestins and CARMA-Bcl10-MALT1 signalosomes. Once internalized, ubiquitinated GPCRs initiate signaling from endosomes via assembly of the transforming growth factor-β-activated kinase binding protein-1 (TAB1)-TAB2-p38 MAPK complex to promote vascular inflammation. Understanding the complexities of GPCR signaling is critical for development of new strategies to treat vascular inflammation such as that associated with COVID-19.